Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1600-0668.2009.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and respiratory symptoms in hospital workers related to dampness and biological contaminants

Abstract: In healthcare facilities with indoor dampness and microbial contamination, possible associations between such conditions and respiratory health effects should be considered. Good building maintenance and housekeeping procedures should lead to improvements in employee respiratory health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 34 publications
2
43
1
2
Order By: Relevance
“…This is confirmed by the existing literature on IAQ (LeBouf et al 2008;Cox-Ganser et al 2009). The indoor environment is characterized by various pollutants, such as airborne dust, volatile organic compounds, molds, and bacteria (Cai et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…This is confirmed by the existing literature on IAQ (LeBouf et al 2008;Cox-Ganser et al 2009). The indoor environment is characterized by various pollutants, such as airborne dust, volatile organic compounds, molds, and bacteria (Cai et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the particle concentrations were generally higher in the indoor air than those reported earlier in the study concerning an office in Espoo, Finland's second biggest city [24]. The particle counts in the indoor air were higher in schools and hospitals situated abroad than in the present study, but the measurement range was also wider (mostly 0.02-1 μm) and, therefore, the direct comparison is not possible [29][30][31][32]. The counts of ≥ 0.5 μm particles in the indoor air were lower (excluding special rooms, e.g.…”
Section: Discussioncontrasting
confidence: 86%
“…Numerous studies have been conducted to investigate indoor biological content (Singh and Singh 1996;Cox-Ganser et al 2009;Rao et al 2007;Salo et al 2008), however, only a limited number of studies have been conducted regarding outdoor microbial content, particularly in the upper atmospheric environments. Fulton (1966) studied the micro-population up to an altitude of 3,127 m and found that the micropopulation was more stable at higher altitude than that at lower altitude.…”
Section: Introductionmentioning
confidence: 99%